Micronutrient deficiency in athletes and inefficiency of supplementation: Is low energy availability a culprit? - Jordan, S. L.; Albracht-Schulte, K.; Robert-McComb, J. J. (PharmaNutrition, 2020)
It is the joint position of the Academy of Nutrition and Dietetics, Dietitians of Canada, and the American College of Sports Medicine that micronutrient supplements are unnecessary for athletes who consume a diet providing high energy availability (EA) from a variety of nutrient-dense foods, but that vitamin and mineral supplements may be necessary in athletes who consume suboptimal amounts of micronutrients. However, inadequate EA, or macronutrient intake needed for energy expenditure associated with exercise, is commonly reported, especially in the female population and may result in micronutrient deficiencies. Moreover, current literature, although limited, reports that athletes` knowledge is lacking regarding adequate macro- and micronutrient intake and needed supplementation. Correction of deficiencies via supplementation may be needed to restore physiologic processes but may not lead to improved performance. Athletes and coaches should be aware of these issues and work together to improve nutrition knowledge and determine if the athlete is at risk for low EA or nutritional deficiencies.